Expression of hes, iha, and tpsA codified in locus of adhesion and autoaggregation and their involvement in the capability of shiga toxin-producing Escherichia coli strains to adhere to epithelial cells - Colello, Rocío (2023)
Objectives: Shiga toxin-producing Escherichia coli strains LAA-positive are important cause of human infection. The capability to adhere to epithelial cells is a key virulence trait, and genes codified in LAA pathogenicity island could be involved in the adhesion during the pathogenesis of LAA-positive STEC strains. Thus, our objectives were to compare hes-negative and hes-positive STEC strains in their adherence capability to epithelial cells (HEp-2) and to evaluate the expression levels of the hes, iha, and tpsA in the bacteria adhered and non-adhered to HEp-2 cells. These genes are encoded in LAA, and are virulence factors that participate in adhesion and autoaggregation. Results: We could not observe differences between the adhesion of strains but also in the expression level of of hes, iha, and tpsA. Genes encoded in LAA contribute to the adhesion phenotype though the expression of STEC adhesins is a coordinated event that depends not only the strain but also on the environment as well as its genetic background. Therefore, the results of this study suggest that LAA ,the most prevalent PAI among LEE-negative STEC strains, plays a role in pathogenesis.